EFFECTS OF ZEOLITE AND SELENIUM APPLICATIONS ON SOME AGRONOMIC TRAITS OF THREE CANOLA CULTIVARS UNDER DROUGHT STRESS - Zahedi, Hossein (2011)
In order to study the effects of zeolite and selenium application on the agronomic traits of three canola cultivars under drought stress conditions, an experiment was conducted in two growing seasons (2006 and 2007). The study site was the Seed and Plant Improvement Institute, in Karaj, Iran. The experimental design was a randomized complete block arrangement, in a split-plot factorial scheme, with three replications. The irrigation factor was applied at two levels: normal irrigation and water holding at the stem elongation stage. Zeolite was used at two levels: non-application and application of 10 t ha-1. Selenium was sprayed at three concentrations: 0 g L-1, 15 g L-1, and 30 g L-1 of sodium selenate. These treatments were randomized in main plots, while three canola cultivars (Zarfam, Sarigol, and Okapi) were randomized as subplots. The results showed that the main effects were significant, while interaction effects were not significant. Irrigation had significant effect on all traits as drought stress lead to a decrease of those traits. Selenium application increased stem diameter, silique and seed number, and seed yield, but it had no significant effect on silique length. Zeolite application provided a significant increase in seed yield and yield components. The cultivars were different in silique and seed number. In general, selenium and zeolite application had significant and positive effect on growth and silique and seed yield. As a result, it can be suggested that the zeolite and selenium application may improve plant growth under drought stress. KEY-WORDS: Brassica napus L.; stem diameter; silique number; seed number; seed yield.